Knowledge of Couples of Reproductive Age with Inspeculo Asam Asetat Examination (IVA): Pengetahuan Pasangan Usia Subur Dengan Pemeriksaan Inspeculo Asam Asetat Examination (IVA) - Ertiana, Dwi; Wahyuni, Wahyuni (Universitas Muhammadiyah Sidoarjo, 2023)
Reproductive health is important for women, cervical cancer which often attacks women. It is a common phenomenon that women's awareness to check IVA screening is still low, this condition is caused by many women who still do not know about IVA screening. The purpose of this study was to determine the relationship between knowledge of couples of childbearing age and IVA examination at the Kedamean Health Center, Gresik Regency. The research design used correlational analysis using a cross-sectional approach. The independent variable of knowledge and the dependent variable of IVA examination is the sampling technique. Simple Random Sampling sample of 52 respondents from 60 couples of childbearing age, place at the Kedamean Health Center, Gresik Regency, May 9-19 2022. Questionnaire sheet instrument. Data analysis using the Spearman test. The results showed that half of the 26 respondents (50%) had good knowledge of IVA examination and the majority of 31 respondents (59.6%) had IVA examination criteria. The results of the analysis obtained a value of ρvalue = 0.000 <α 0.05. This indicates that H1 is accepted, a relationship between the knowledge of couples of childbearing age and IVA examination at the Kedamean Health Center, Gresik Regency, with a value of (r) 0.739. Knowledge can underlie behavior change, as the IVA examination can be influenced by the mother's knowledge, the better the knowledge, the more willing the mother is to carry out the IVA examination.